Malachite green dye behaviors in the presence of biosorbents from maize (Zea mays L.), their Fe-Cu nanoparticles composites and Fe-Cu nanoparticles. Issue 2 (June 2016) - Lara-Vásquez, E.J.; Solache-Ríos, M.; Gutiérrez-Segura, E.
Abstract: The sorption behaviors of biosorbent based on maize ( Zea mays, ZM) cane (bagasse and stalk), their composites (ZM/Fe-Cu nanoparticles) and Fe-Cu nanoparticles for malachite green from aqueous solutions were investigated in this work. Adsorbents were characterized using BET, infrared spectroscopy, X-ray diffraction, SEM-EDS, and Fe-Cu nanoparticles were characterized by TEM. The study of the sorption kinetics indicates that the adsorption on malachite green by stalk and their composite follows second-order kinetics and nanoparticles and bagasse and their composite follow the pseudo-second order model. The malachite green adsorption by ZM/Fe-Cu composites were faster than natural materials and only showed two phases in the intraparticle diffusion model, probably due to the minor internal diffusion resistance. The adsorption isotherms experimental data were analyzed by the Langmuir, Freundlich and Langmuir–Freundlich models and the equilibrium data was well described by the Langmuir–Freundlich isotherm model. The adsorption was more favorable at basic pH. The OH- groups were proportional to dye adsorption capacities. Results showed that composites (ZM/Fe-Cu nanoparticles) and Fe-Cu nanoparticles possessed good adsorption abilities to malachite green.